Correlation Between Adherence Therapy of Iron Chelation Levels with Anthropometric Status in Major Beta-Thalassemia Patients - Dwi Kartika Sari, Grafita; Diyah Permatasari, Trinita; Ismail, Chasan (Indonesian Health Journal, 2023)
Thalassemia is a condition in which hemoglobin undergoes hemolysis due to impaired synthesis of hemoglobin or globin chains. Growth failure is a common occurrence in patients with thalassemia. Iron overload due to repeated transfusions will cause disturbances in anthropometric status in children with thalassemia. Iron chelation therapy is needed to overcome iron overload in patients with beta-thalassemia major. The level of adherence affects the success of iron chelation therapy. This study aims to determine the relationship between the level of adherence to iron chelation treatment and anthropometric status in patients with thalassemia beta major at Kediri District General Hospital. This type of research is observational analytic with a cross-sectional design. This research was conducted at the SMF Pediatrics (IKA) RSUD Kediri Regency on 16 subjects with B-thalassemia major using a total sampling technique that met the inclusion criteria. The research instruments used in this study were the Morisky Medication Adherence Scale-8 questionnaire and an examination of anthropometric status. The research analysis used the Spearman correlation test. A p-value <0.05 was considered significant. The results showed that there was a significant results between adherence to iron chelation consumption and height for age (p-value = 0.049 > a 0.05), significant results between adherence to iron chelation consumption with weight for age (p-value = 0.036 < a 0.05), and significant results with weight for height (p-value = 0.001 < a 0.05). This study implies that adherence to iron chelation therapy is essential for thalassemia patients. This study shows that patients more adherent to iron chelation treatment have better anthropometric status.